Policy Perception and Implementation Satisfaction as Dual Mediators of Student Retention in Multi-Faith Higher Education: A PLS-SEM Study - Hesti Sadtyadi; Santi Paramita (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study examines the implementation of the Single Tuition Fee policy at a multi-faith religious higher education institution. This study analyzes student perceptions and satisfaction across various dimensions, identifies causal mechanisms among student characteristics, policy perceptions, implementation satisfaction, and study continuation, and examines the implementation challenges faced by the institution. Methodology: A mixed-methods sequential explanatory design was employed. Quantitative survey of 159 students (80% response rate) analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Qualitative data collected through focus groups and interviews. Validated questionnaires measured transparency, accessibility, affordability, responsiveness, and the impact of study continuity. Main Findings: Results revealed 90% of students would be unable to pursue higher education without the Single Tuition Fee support. Students rated transparency highest (M=4.1), followed by responsiveness (M=3.9), accessibility (M=3.8), study continuity (M=3.7), and affordability (M=3.6). The structural model demonstrated that policy perception strongly influenced implementation satisfaction (β=0.695, p<0.001), which, in turn, significantly affected study continuity (β=0.548, p<0.001). Student characteristics shaped policy perception (β = 0.452, p < 0.001), with full mediation through perceptions and satisfaction. Novelty/Originality of this study: First comprehensive evaluation of the Single Tuition Fee policy implementation in religious higher education using PLS-SEM methodology. Reveals that policy success operates through a causal chain in which positive perceptions and high-quality implementation matter as much as financial support itself, advancing understanding of the effectiveness of higher education financing in minority religious institutions.